Pakistan’s Efforts to Enhance Its Geo-Economic Potential through Collaboration with China - Fazal, Iqra; Khan, Waheed Ahmad (Annals of Human and Social Sciences, 2023)
Over the last couple of decades, Pakistan’s foreign policy emphasis has shifted away from traditional security-centric focus to a more geo-economically oriented strategy. China has emerged as a key player in Pakistan’s geo-economic strategy, owing principally to its flagship project, the China-Pakistan Economic Corridor (CPEC). As a part of China’s ambitious Belt and Road Initiative (BRI), CPEC intends to expand infrastructure, energy, and industrial projects in Pakistan, promoting economic growth and regional integration. Pakistan’s decision to join CPEC is analyzed in detail to determine if Pakistan joined this project to boost relations with China, enhance its economic growth, or to gain geo-economic benefits. Through study of documents related to CPEC and expert interviews, it was found that China’s economic investments in Pakistan have contributed to Pakistan’s economic growth. However, Pakistan’s main intention to join CPEC was to enhance its geo-economic potential, especially vis-à-vis regions to its North, Northeast, and East.